PERAN WALK FREE FOUNDATION (WFF) DALAM MENGATASI MODERN SLAVERY DI MAURITANIA - Endah Artika Noerilita; Saiman Pakpahan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
This research is a study of contemporary which discuss about the role of the Walk Free Foundation (WFF) in handling modern slavery in Mauritania. Slavery has been existed in Mauritania since European performed a trading contact with the African. Modern slavery is a condition of one person possessing or controlling another person in such as a way as to significantly deprive that person of their individual liberty, with the intention of exploiting that person through their use, management, profit, transfer or disposal. Modern slavery includes slavery, slavery-like practices (such as debt bondage, forced marriage and sale or exploitation of children), human trafficking and forced labour, and other practices described in key international treaties, voluntarily ratified by nearly every country in the world. The form of modern slavery in Mauritania is slavery based descent, also known as hereditary or chattel slavery, mean that slave status is inherited generation to generation and is deeply rooted in social castes and the wider social system. Many victims are the Black Moors (black African) came from both rural and urban areas. Actually, modern slavery not only occurs in Africa but also in other countries such as Asia and Europe. In this research, the author is using the group behavior analysis level which focused on the role of international organization. This research is using a pluralism perspective in international relations and organizational theory of Clive Archer. WFF’s role in handling modern slavery in Mauritania by prevention program. In efforts to handle modern slavery in Mauritania, WFF faces some obstacles; the lack of public knowledge about the dangers of modern slavery, lack of resource capacity in Mauritania and lack of monitoring and evaluation of the Mauritanian government cause the victims of modern slavery increase from year to year.Keywords: slavery, modern slavery, mauritania, walk free foundation (wff), global slavery index (gsi), walkfree movemenT.